The Effectiveness of Using Flashcard My Dance Adventure Media in Introducing Javanese Traditional Dance to Class B Students of RA Matholibul Ulum 01 - Anjani, Sheila Putri; Nugroho, Agustinus Arum Eka (Jurusan PGPAUD FIP UNNES, 2024)
Flashcard my dance adventure media is one of learning media that can be used by teachers to students in order to introduce Javanese traditional dance. Introduce various Javanese traditional dances from various provinces in Java Island gave a new introduction to students about traditional dance arts in Indonesia to foster a sense of love for the arts and culture of the nation. The confusion occurred to students about Javanese traditional dance itself, both in terms of the traditional dance regional origin, costumes, and the story behind every traditional dance. This research aims to find out whether the use of flashcard my dance adventure media are able to increase the student’s recognition toward Javanese traditional dances in RA Matholibul Ulum 01. This research used quantitative approach that is experimental research that used One Group Pretest Posttest as the research design. The population is the whole students of RA Matholibul Ulum 01 as many as 30 students. The data collection technique used observation, questionnaire, and documentation. The data analysis used in this study are descriptive analysis and hypothesis test through paired sample t-Test test technique. The result of t test calculation obtained score tcount ≥ ttable as many as 28,793 > 2,045 with the significant value (2 tailed). So, Ha is accepted that there is a significant difference related to flashcard my dance adventure use to increase students’ recognition abilities toward Javanese traditional dances. There is a difference from the average pretest is 71,23 after being given posttest treatment increased become 112,87 and obtained a significant enhancement that is equal to 41,64. The N-Gain test result obtained 0,54 showed that flashcard my dance adventure media is effective to introduce Javanese traditional dances to class B students of Matholibul Ulum 01 with medium category. Keywords: Flashcard My Dance Adventure, Recognition abilities, Javanese Traditional Dance.